The EFFECTIVENESS TEST OF Cordyceps militaris FUNGUS AGAINST FIREWORM Setothosea asigna - Ginting, Makhrani Sari; Simbolon, Hasanal Fachri Satia; Nurliana; Dibisono, Muhammad Yusuf; Wanda Sandy Pratama (Agro Estate, 2024)
Oil palm industry is an important source of Indonesian income. In its cultivation, oil palm plants also face some challenges, one of which is the attack of fireworm Setothosea asigna.  Fireworms are insects that can cause serious damage to oil palms. Various efforts were often made to control fireworm, one of which is by using biological agents such as the Cordyceps militaris fungus. The aim of this research is to determine the effectiveness of  C. militaris fungus against S. asigna. The research was carried out in the Experimental  Area of ​​Institut Teknologi Sawit Indonesia, from March to May 2024, using the Non-Factoral Randomized Block Design (RBD) with 5 treatments, namely F0/Control (without application of C. militaris), F1 (application C. militaris 15 grams/1 liter of water), F2 (application of C. militaris 20 grams/1 liter of water), F3 application of C. militaris 25 grams/1 liter of water) and F4 (application of C. militaris 30 grams/1 liter of water) with 5 repetitions. Data obtained was analyzed by using Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT). Result showed that C. militaris fungus was effective in controlling S. asigna. In this research the most effective concentration of  C. militaris fungus in controlling S. asigna was 30 grams/1 liter of water (F4), where in this treatment mortality 100% and LT50 occurs faster than in treatments F0, F1, F2 and F3.